Unsteady aerodynamics of a coupled compact intake-fan in crosswind - Lobuono, Luca; MacManus, David G.; Christie, Robert; Boscagli, Luca (International Council of the Aeronautical Sciences (ICAS), 2024)
The design of aero-engine intakes for compact nacelles can be an important contributor in achieving cruise fuel burn reductions. A key aspect for the design of viable compact intakes is considerations of the off-design crosswind and high incidence conditions. The aerodynamics of compact intakes is also notably dependent on the flow interaction with the fan. This work analyses the unsteady intake-fan interactions under crosswind conditions. The effect of crosswind velocity is evaluated together with the intake ground plane interaction and the unsteady aerodynamic coupling between the intake and fan. The overall aim of the research is to identify the flow structures and the unsteady mechanisms involved in the separation of the intake flow. The work uses an unsteady fully coupled time resolved Reynolds averaged Navier-Stokes computational method to identify the unsteady features of intake-fan flow separation in crosswind operations. The unsteady intake flow distortion is assessed as well as the spectral signatures and engine-order perturbations due to the unsteady flow distortion. Local separated regions were identified in the diffuser. These are associated with the characteristics of the boundary layer and are phase-locked with the local pressure pulses from the fan. This aspect should be considered in the design of compact intakes with relatively high diffusion. Additional assessments of the previously reported unsteady lip separation is provided with the identification of the frequencies of the flow features in post-separation conditions and the axial and azimuthal movement of the separation due to the interaction with the ground vortex.
Keywords: Aerodynamics; crosswind; fan; ground effect; intake